Childhood overweight and obesity abatement policies in Europe. (4th November 2021) - Wickramasinghe, Kremlin; Chatterjee, Saion; Williams, Julianne; Weber, Martin W.; Rito, Ana Isabel; Rippin, Holly; Breda, João
Summary: Over the past two decades, a concerted effort to combat the rising tide of childhood overweight and obesity has taken shape. The World Health Organization (WHO) Commission on Ending Childhood Obesity (ECHO) provides recommendations for six priority areas of action, including the promotion of healthy food consumption, promotion of physical activity, preconception and pregnancy care, early childhood diet and physical activity, healthy nutrition and physical activity for school‐aged children, and community‐based weight management. This paper provides a snapshot of policies and measures aligned to these areas of action within the WHO European Region in order to encourage other countries to make similar efforts. Examples are drawn from Portugal (sugar‐sweetened beverage tax, integrated nutrition strategy), the United Kingdom (soft drink levy, active commuting programs, urban design principles), Lithuania (prohibition of energy drinks), Norway (industry and government partnerships to promote healthier foods, nutrition education curriculum for schools), Hungary (tax subsidies to promote healthy diets), the European Union (cross‐border marketing regulations, preconception and pregnancy care), Slovenia (food marketing restrictions), Spain (marketing restrictions within educational settings), Poland (investing in sports infrastructure), Russia (increasing sports participation), Estonia (redevelopment of the physical education curriculum), Netherlands (preconception and pregnancy care), Croatia (conditions to support breastfeeding), Austria (perinatal and early childhood nutrition), Czechia (life‐course strategy), San Marino (nutrition and physical activity for school‐aged children), Ukraine (potable water for schools), Ireland and Italy (community‐based weight management approaches). Our findings suggest that a large disparity exists among the type and breadth of policies adopted by Member States, with a mix of single‐issue policy responses and more cohesive strategies. The role of data, implementation research, and ongoing surveillance of country‐level progress related to childhood overweight and obesity policies are discussed as an essential part of the iterative process of policy development. Additional work to systematically gather context‐specific information on policy development, implementation, and reach according to ECHO's six areas of action by WHO European Region countries will inform future policy paradigms within the region.